BIOLOGI HAMA KUTU PUTIH PEPAYA (Paracoccus marginatus) PADA TANAMAN PEPAYA - Hartati Oktarina; Nur Pramayudi (Jurnal Floratek, 2012)
Mealybug (Paracoccus marginatus) is a new pest attacted papaya that effect quantity and quality of papaya production. The research was aimed at study of biology and development of papaya mealy bug; from an egg stadium to mature bug. The experiment was conducted at plant field experiment of Agriculture Faculty, Syiah Kuala University from May to November 2011. To understand the biology and development of mealy bug, a survey and collection of P. Marginatus were conducted for mass production in laboratory, then they were invested on healthy papaya leaf. In the future the result of this study will be used as a pest control recommendation.